Byron and romanticism - McGann, Jerome J.; Soderholm, James, 1957- (Cambridge, UK ; New York : Cambridge University Press, 2002)
This collection represents twenty-five years of work by Jerome McGann, one of the most important critics of Romanticism and Byron studies. Many of these essays have previously been available only in specialist scholarly journals. Now McGann's influential work on Byron can be appreciated more widely by new generations of students and scholars.
Milton and Byron -- Byron, mobility, and the poetics of historical ventriloquism -- My brain is feminine': Byron and the poetry of deception -- What difference do the circumstances of publication make to the interpretation of a literary work? -- Byron and the anonymous lyric -- Private poetry, public deception -- Hero with a thousand faces: the rhetoric of Byronism -- Byron and the lyric of sensibility -- Byron and Wordsworth -- A point of reference -- History, herstory, theirstory, ourstory -- Literature, meaning, and the discontinuity of fact -- Rethinking romanticism -- An interview with Jerome McGann -- Poetry, 1780-1832 -- Byron and romanticism, a dialogue (Jerome McGann and the editor, James Soderholm).
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Byron, George Gordon Byron, -- Baron, -- 1788-1824 -- Criticism and interpretation; Byron, George Gordon Byron, -- baron, -- 1788-1824 -- Critique et interprétation.; Byron, George Gordon Byron, -- Baron, -- 1788-1824; Romanticism -- England; Romantisme -- Angleterre; POETRY -- English, Irish, Scottish, Welsh; Romanticism; England; Electronic books; Criticism, interpretation, etc